Internalisasi Nilai Kearifan Lokal dalam Keilmuan Bimbingan dan Konseling - Hidayat, Ade (Universitas Mathla'ul Anwar Banten, 2023)
World life which is constantly changing rapidly requires the presence of realistic studies and views by paying attention to local wisdom. In the academic field, especially education today, which is characterized by decentralization and autonomy, it gives a pedagogical orientation to the trend of multiculturalism. The orientation of Indonesian education is directed at the nation's motto “Bhineka Tunggal Ika”, Unity in Diversity, meaning that the blueprint for Indonesian education must be based on a philosophical and cultural basis which guarantees that Indonesian people are dignified and sovereign who are not uprooted from their cultural roots as an Indonesian nation. Guidance and counseling as an integral part of education requires a strong philosophical foundation based on the abstraction of environmental and local cultural values. For guidance and counseling, the philosophical foundation provides directions for scientific development as general competence, code of ethics, and practice of guidance and counseling services. Directions are needed as a guide in facing such rapid and complex changes in life.